2007
DOI: 10.1111/j.1526-100x.2007.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Prairie Community Structure and Ecosystem Function in an Abandoned Hayfield: A Sowing Experiment

Abstract: Using a multispecies seed sowing experiment, we investigated the roles of seed and microsite limitation in constraining the restoration of native prairie diversity and ecosystem function in an abandoned upland hayfield in northeastern Kansas. Seeds of 32 native and naturalized plant species from the regional pool were sown into undisturbed and experimentally disturbed field plots. After six growing seasons, experimental sowing led to major shifts in species and functional group composition, increases in native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 55 publications
3
93
1
8
Order By: Relevance
“…At the same time, a negative correlation between non-native grasses and native graminoids and increasing native graminoid cover (Figure 1) illustrate competition that may lead towards a transition from non-native grass-dominated to native graminoid-dominated communities. Similar results have been found by Foster et al (2007), in which sowing of native and naturalized prairie species decreased non-native grass, including the most common non-native grass species found during our study, Kentucky bluegrass. Endress et al (2012) found that while seeding native grasses into an invasive forb-dominated community lowered non-native grass cover within six years, cover of the dominant invasive forb was unaffected.…”
Section: Seeding Effectssupporting
confidence: 78%
See 1 more Smart Citation
“…At the same time, a negative correlation between non-native grasses and native graminoids and increasing native graminoid cover (Figure 1) illustrate competition that may lead towards a transition from non-native grass-dominated to native graminoid-dominated communities. Similar results have been found by Foster et al (2007), in which sowing of native and naturalized prairie species decreased non-native grass, including the most common non-native grass species found during our study, Kentucky bluegrass. Endress et al (2012) found that while seeding native grasses into an invasive forb-dominated community lowered non-native grass cover within six years, cover of the dominant invasive forb was unaffected.…”
Section: Seeding Effectssupporting
confidence: 78%
“…Mowing allowed for comparable levels of seeded species cover as both herbicide treatments, with the exception of lower big bluestem cover (Table 4), which should be temporary due to the dominant nature of this species (McCain et al 2010). Yet, the ease with which native grasses and forbs established following such minimal site preparation indicates that seed limitations may be preventing natural recovery of some degraded sites (Foster et al 2007), and shows promise for the development of communities with this treatment. As reported by MacDonald et al (2013), the single mowing had few effects on knapweed densities on mowed-only plots, with a total knapweed density of 251 ± 47 m-2 (mean ± SE) in 2010, and remaining at a comparable level in 2011 (218 ± 38 m-2).…”
Section: Initial Site Preparation Effectsmentioning
confidence: 99%
“…Finally, it is likely that the recovery potential varies substantially for different systems depending on the life history of the species of interest, the presence of refuge populations, and a host of other factors (Clark and Tilman 2010). However, several long-term studies to date suggest that recovery over small scales can be slow and require intervention (Foster et al 2007, Clark and Tilman 2010, Isbell et al 2013. Considering anthropogenic N deposition occurs over large spatial scales, making the presence of refugia unlikely, reduction of current N loads is preferred before potentially intensive management options are considered.…”
Section: Christopher M Clark Et Al 1444mentioning
confidence: 99%
“…In recent years, the potential benefits of native tallgrass prairie vegetation has been increasingly recognized by conservationists, private landowners, and the general public in terms of conservation value for biodiversity, wildlife habitat, soil protection, and a range of other ecosystem services and aesthetic values (Baer et al 2002, Tunnell 2004, Polley et al 2005, Foster et al 2007). In addition, there is growing interest in the potential use of low-input, high-diversity (LIHD) grasslands, such as tallgrass prairie or prairie hay meadows for biofuel production , Wallace and Palmer 2007, Fargione et al 2008.…”
Section: Introductionmentioning
confidence: 99%